Prognostic value of elevated cardiac troponin in aneurysmal subarachnoid hemorrhage: a systematic review and meta-analysis - Zhao, Jiahui; Gu, Shujuan; Zhao, Xudong; Wang, Shisong; Pan, Qichen; Zou, Cunyi (Frontiers in Neurology, 2025)
ObjectiveSubarachnoid hemorrhage (SAH) is a common intracranial hemorrhagic condition associated with a high mortality rate and significant disability due to serious complications. In clinical practice, we have observed that elevated serum cardiac troponin (cTn) levels correlate with a poor prognosis in SAH. Although some studies have reported this correlation, these studies had small sample sizes and did not make a distinction between traumatic SAH and aneurysmal SAH. Accordingly, we aimed to systematically analyze the prognostic evaluation value of elevated cTn levels in SAH by reviewing all existing studies to provide a clinical reference.MethodsWe selected studies on cTn and SAH from PubMed, Medline, Embase, Web of Science, Cochrane Library, and Clinical Trails databases published before December 2023. The Newcastle–Ottawa Scale was used to evaluate the quality of the included studies. PRISMA and AMSTAR guidelines were followed to assess the methodological quality of the systematic review. We divided the included studies into two groups: aneurysmal subarachnoid hemorrhage (aSAH) group and total subarachnoid hemorrhage (toSAH) group. The total subarachnoid hemorrhage (toSAH) group included aSAH and traumatic SAH studies for analysis. The pooled effect size was calculated using R studio and Stata 14.0.ResultsIn the toSAH group, 1,559 out of 6,349 (24.55%) SAH patients from 33 studies exhibited elevated cTn levels, while 25.0% in the aSAH group also exhibited similar results. In the aSAH group, high levels of cTn were significantly related to increased mortality both in the hospital [OR = 2.51, 95%CI (1.95, 3.23)] and 3 months later [OR = 2.27, 95%CI (1.47, 3.49)]. An increased incidence of disturbance of consciousness [OR = 2.28, 95%CI (1.41, 3.67)], delayed cerebral ischemia (DCI) [OR = 1.99, 95%CI (1.40, 2.83)], physical disability [OR = 2.39, 95%CI (1.79, 3.20)], cardiac dysfunction [OR = 3.97, 95%CI (2.95, 5.33)], arrhythmias [OR = 4.87, 95%CI (2.52, 9.41)], abnormal ventricular wall motion [OR = 8.20, 95%CI (3.70, 18.18)], and neurogenic pulmonary edema [OR = 2.76, 95%CI (1.85, 4.12)] were associated with elevated cTn levels. In the total SAH patient group, the results were further validated.ConclusionElevated cTn levels were associated with a poor prognosis and an increased risk of adverse events, particularly in aneurysmal SAH. Clinicians should prioritize monitoring SAH patients with elevated cTn levels and consider early intervention strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023433744, identifier: CRD42023433744.